Effects of instructing WHO’s guidelines regarding postpartum hemorrhage on knowledge and practice of midwives - Masoumi, Z; Khatiban, M; Garoosian, M (Advances in Nursing & Midwifery, 2009)
Background and aim Each year, many women in developing countries including Iran die of postpartum hemorrhage. As a result, in 2007, WHO emphasized on instruction of correct principles in delivery attendants. This quasi-experimental study was conducted to determine and compare the effects of instructing WHO’s guidelines on knowledge and practice of midwives of Fatemiyeh Hospital in Hamedan city. Materials and methods All midwifery personnel of the hospital took part in the study. They were instructed theoretically and practically regarding WHO standards in 10 sessions. Data collection tools included a pretest, a posttest and an observation checklist for practice. Content and test-retest methods were used for validity and reliability of the tools respectively. Findings A significant difference was found between knowledge (P<0.001) and practice (P<0.004) of the personnel before and after the instruction. Conclusion Instructing the correct principles for controlling postpartum hemorrhage can improve knowledge and practice of personnel. Thus, more extensive educational programs are recommended. Keywords: Postpartum hemorrhage, Knowledge, Practice, Midwife. *Corresponding Author: Dr. Khatiban; Assistant Professor, Faculty of Nursing and Midwifery, Hamedan Medical University, Iran. *(Corresponding Author) Email: mkhnurse@yahoo.com